Biomarkers of sepsis associated encephalopathy: a bibliometric and visualized analysis - Qi, Chuyao; Liu, Yanfei; Hua, Tianfeng; Yang, Min; Liu, Yue (Frontiers in Neurology, 2025)
ObjectivesThis study employs bibliometric analysis to investigate the current states and emerging trends in the field of sepsis associated encephalopathy biomarkers. It conducts a comparative analysis of the research contributions from different countries, institutions, journals and authors, thereby providing a valuable reference for future investigations in this field.MethodsAll publications on sepsis associated encephalopathy biomarkers research were retrieved and extracted from the China National Knowledge Infrastructure Database and the Web of Science Core Collection on December 31st, 2024. Microsoft Office Excel was used to conduct quantitative analysis of related studies data. VOSviewer, CiteSpace and R package “bibliometrix” were used to conduct the bibliometric analysis.ResultsThis study included 248 articles from 36 countries, with China and the United States identified as the primary contributors. The number of publications concerning sepsis associated encephalopathy biomarkers has been progressively rising on an annual basis. Santa Catarina State University, University of Texas Health Science Center at Houston and University of Texas System are the primary research institutions. The largest number of publications appeared in Molecular Neurobiology. Critical Care Medicine is the most co-cited journal. These publications contributed by 1,234 authors among which Felipe Dal-pizzol, Tatiana Barichello and Fabricia Petronilho had published numerous articles and Felipe Dal-pizzol was the most frequently co-cited. “Neuron specific enolase,” “protein” and “oxidative damage markers” are the primary keywords of emerging research hotspots.ConclusionThis is the first thorough bibliometric study to summarize the developments and trends of sepsis associated encephalopathy biomarkers research since the inception of the China National Knowledge Infrastructure Database and the Web of Science Core Collection. These findings identify recent research hotspots, which will provide a reference for scholars studying sepsis associated encephalopathy biomarkers in the future.